Community Resilience in Ecotourism Associations in Peruvian Hills: A Collective Fight Against the Covid-19 - Cordova-Buiza, Franklin; Huerta-Tantalean, Lucero Nicole; Bermejo-Tipiani, Paola Aurora; Gabriel-Campos, Edwin (CENTRAL ASIA AND THE CAUCASUS, 2021)
Only in South America surrounded by the Pacific Ocean are coastal hills, natural areas formed by the action of fog, located. Near these ecotourism places are established community associations that are focused on the preservation and development of the natural heritage and currently they are in the process of adaptation to the biological crisis. The present study aims to analyze the main indicators developed by two ecotourism community associations in Peru to achieve community resilience to the Covid 19 pandemic, in 3 phases of the disaster and / or crisis: pre- disaster, response and recovery; allowing its replicability and improvement in other community associations belonging to the Peruvian Hills Network or other community associations from different geographical areas in the world. Focus groups and interviews were held with representatives, members of community associations and members of the Peruvian Hills Network. It was observed that the sense of community and community participation are the most influential and developed indicators in community resilience, unlike education, coping style, and improvisation and inventiveness. In addition, it was concluded that these community associations have a good level of resilience to face the pandemic; however, it is necessary to improve aspects of internal coordination, as well as work together with the authorities.